Fat-Intrabody communication at 5.8 GHZ: Verification of dynamic body movement effects using computer simulation and experiments - Asan, Noor Badariah; Augustine, Robin; Hassan, Emadeldeen; Perez, Mauricio David; Joseph, Laya; Berggren, Martin; Voigt, Thiemo (Institute Of Electrical And Electronics Engineers Inc., 2021)
This paper presents numerical modeling and experimental validation of the signal path loss at the 5.8 GHz Industrial, Scientific, and Medical (ISM) band, performed in the context of fat-intrabody communication (fat-IBC), a novel intrabody communication platform using the body-omnipresent fat tissue as the key wave-guiding medium. Such work extends our previous works at 2.0 and 2.4 GHz in the characterization of its performance in other useful frequency range. In addition, this paper also includes studies of both static and dynamic human body movements. In order to provide with a more comprehensive characterization of the communication performance at this frequency, this work focuses on investigating the path loss at different configurations of fat tissue thickness, antenna polarizations, and locations in the fat channel. We bring more realism to the experimental validation by using excised tissues from porcine cadaver as both their fat and muscle tissues have electromagnetic characteristics similar to those of human with respect to current state-of-art artificial phantom models. Moreover, for favorable signal excitation and reception in the fat-IBC model, we used topology optimized waveguide probes. These probes provide an almost flat response in the frequency range from 3.2 to 7.1 GHz which is higher than previous probes and improve the evaluation of the performance of the fat-IBC model. We also discuss various aspects of real-world scenarios by examining different models, particularly homogeneous multilayered skin, fat, and muscle tissue. To study the effect of dynamic body movements, we examine the impact of misalignment, both in space and in wave polarization, between implanted nodes. We show in particular that the use of fat-IBC techniques can be extended up in frequency to a broadband channel at 5.8 GHz